The Effect of Employee Engagement and Job Satisfaction on Workforce Agility Through Talent Management in Public Transportation Companies - Ahmad Azmy (Media Ekonomi dan Manajemen, 2021)
This study aimed to analyzed employee engagement and job satisfaction with workforce agility through talent management as a mediating variable. The object of research was carried out at one of the public transportation companies. The number of respondents was 100 people. This research is purposive because it is following the research needs. The analysis tool uses the Partial Least Square (PLS) method. It aims to analyze specifically the variables and indicators that affect workforce agility. The results showed that employee engagement and job satisfaction had a positive effect on workforce agility. The role of talent management as a mediating variable affects workforce agility. Organizations must maximize the role of talent management to prepare employee competencies according to business challenges. The implementation of employee engagement and job satisfaction will make employees more agile, responsive, and have high initiatives to generate business innovation. Job satisfaction is very much needed in maintaining performance stability. The business process is very dependent on how the role and involvement of employees in executing the business plan. The four variables explain that workforce agility makes employee responsiveness higher in advancing the company's business. Therefore, organizations must be responsive and adaptive in empowering human resources optimally